Regional adaptation of the education in palliative and end‐of‐life Care Pediatrics (EPEC‐Pediatrics) curriculum in Eurasia. (8th September 2022) - McNeil, Michael J.; Ehrlich, Bella; Yakimkova, Taisiya; Wang, Huiqi; Mishkova, Volha; Bezler, Zhanna; Kumirova, Ella; Madni, Arshia; Movsisyan, Narine; Williams, Karen; Baizakova, Baglan; Borisevich, Marina; et al.
Abstract: Background: Pediatric palliative care (PPC) is a priority to improve pediatric hematology oncology (PHO) care in Eurasia. However, there are limited regional opportunities for PPC education. We describe the adaptation and implementation of a bilingual end‐user Education in Palliative and End‐of‐Life Care (EPEC)‐Pediatrics course for PHO clinicians in Eurasia. Methods: Due to COVID‐19, this course was delivered virtually, consisting of prerecorded, asynchronous lectures, and a bilingual workshop with interactive lectures and small group sessions. A pre–postcourse design was used to evaluate the knowledge acquisition of the participants including their knowledge alignment with World Health Organization (WHO) guidance, ideal timing of palliative care, and comfort in providing palliative care to their patients. Questions were mostly quantitative with multiple choice or Likert scale options, supplemented by free‐text responses. Results: A total of 44 (76%) participants from 14 countries completed all components of the course including pre‐ and postcourse assessments. Participant alignment with WHO guidance improved from 75% in the pre‐ to 90% in the postcourse assessments ( p < 0.001). After participation, 93% felt more confident controlling the suffering of children at the end of life, 91% felt more confident in prescribing opioids and managing pain, and 98% better understood how to hold difficult conversations with patients and families. Most participants (98%) stated that they will change their clinical practice based on the skills and knowledge gained in this course. Conclusions: We present a successful regional adaptation of the EPEC‐Pediatrics curriculum, including novel delivery of course content via a virtual bilingual format. This course resulted in significant improvement in participant attitudes and knowledge of PPC along with an understanding of the ideal timing of palliative care consultation and comfort in providing PPC to children with cancer. We plan to incorporate participant feedback to improve the course and repeat it annually to improve access to high‐quality palliative care education for PHO clinicians in Eurasia. Abstract : A lack of formal education in pediatric palliative care for clinicians caring for children in resource‐constrained settings remains a significant challenge. We successfully adapted the Education in Palliative and End‐of‐Life Care (EPEC) ‐ Pediatrics course for clinicians in Eurasia and demonstrate the course significantly improved provider knowledge and comfort in palliative care principles.